2019
DOI: 10.14712/18059694.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-6 −174 G>C Polymorphism with Susceptibility to Colorectal Cancer and Gastric Cancer: a Systematic Review and Meta-Analysis

Abstract: Background: The −174G>C (rs1800795) polymorphism at interleukin 6 (IL-6) gene has been reported to be related with the occurrence of colorectal (CRC) and gastric (GC) cancers. However, the results had been conflicting and controversial. In order to give a comprehensive and precise result, we summarized available data to analyze the association of this polymorphism with CRC and GC risk. Methods: A comprehensive literature search on PubMed, Elsevier Science Direct, and CNKI database was performed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Finally, 39 case-control studies including 7 studies with 2005 cases and 2,748 controls were on PON1 rs662, 6 studies with 2,031 cases and 1,973 controls on PON1 rs854560, 12 studies with 3,444 cases and 3,583 controls on LEP rs7799039, and determined by Z-test, in which P<0.05 was considered statistically significant. The associations was evaluated under all five genetic models, i.e., allele (B vs. A), homozygote (BB vs. AA), heterozygote (BA vs. AA), dominant (BB+BA vs. AA), and the recessive (BB vs. BA+AA), in which ''B'' presents mutant and ''A'' wild allele (Jafari-Nedooshan et al, 2019;Jafari et al, 2020). Between-study heterogeneity was estimated using a Cochran-based Q statistical test, with P-values less than 0.1 indicated the absence of indicated heterogeneity among studies.…”
Section: Selected Studies Characteristicsmentioning
confidence: 99%
“…Finally, 39 case-control studies including 7 studies with 2005 cases and 2,748 controls were on PON1 rs662, 6 studies with 2,031 cases and 1,973 controls on PON1 rs854560, 12 studies with 3,444 cases and 3,583 controls on LEP rs7799039, and determined by Z-test, in which P<0.05 was considered statistically significant. The associations was evaluated under all five genetic models, i.e., allele (B vs. A), homozygote (BB vs. AA), heterozygote (BA vs. AA), dominant (BB+BA vs. AA), and the recessive (BB vs. BA+AA), in which ''B'' presents mutant and ''A'' wild allele (Jafari-Nedooshan et al, 2019;Jafari et al, 2020). Between-study heterogeneity was estimated using a Cochran-based Q statistical test, with P-values less than 0.1 indicated the absence of indicated heterogeneity among studies.…”
Section: Selected Studies Characteristicsmentioning
confidence: 99%
“…The results obtained in this study can provide a statistical basis for elucidating the genetic mechanism of GC incidence, and provide reference for the study of GC treatment drugs and some inhibitors. Previous studies (Wang et al, 2012(Wang et al, , 2018bYin et al, 2012;Attar et al, 2017;Dos Santos et al, 2019;He et al, 2019;Jafari-Nedooshan et al, 2019) reported the relationship between IL-6 gene SNPs and GC risk, however, these studies concluded inconsistent results. A case-control study performed in an Iranian population suggested that IL-6 -rs1800795 polymorphism was significant associated with the GC susceptibility, the rs180079-5 G allele was associated with higher GC susceptibility (Attar et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Meta-studies (Wang et al, 2012;Yin et al, 2012;Dos Santos et al, 2019) suggested that rs1800795, rs1800796, rs1800797 polymorphism was NS associated with susceptibility to GC. Jafari-Nedooshan et al (Jafari-Nedooshan et al, 2019) performed a meta-analysis and suggested that rs1800795 was not associated with the GC risk, but this relationship was statistically significant in Asians (CC vs. CG + GG). Another case-control (He et al, 2019) and meta-study (Wang et al, 2018b) indicated that rs1800796 (-572C/G) was not associated with GC risk in overall populations but was associated with increased GC risk in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…There was growing evidence that inflammatory responses also played significant roles in solid malignancies. For example, interleukin-6 (IL-6), a common pro-inflammatory factor, promoted tumor cell proliferation, invasiveness, and metastasis, and affected the clinical prognosis in various solid malignancies including gastric cancer [12][13][14][15] . However, pro-inflammatory factors did not always play the roles of "pro-oncogenic factors".…”
Section: Il-6/il-10 Mrna Expression Ratio In Tumor Tissues Predicts P...mentioning
confidence: 99%